Flow Control Methods and Their Applicability in Low-Reynolds-Number Centrifugal Compressors—A Review - Jonna Tiainen; Aki Grönman; Ahti Jaatinen-Värri; Jari Backman (International Journal of Turbomachinery, Propulsion and Power, 2017)
The decrease in the performance of centrifugal compressors operating at low Reynolds numbers (e.g., unmanned aerial vehicles at high altitudes or small turbomachines) can reach 10% due to increased friction. The purposes of this review are to represent the state-of-the-art of the active and passive flow control methods used to improve performance and/or widen the operating range in numerous engineering applications, and to investigate their applicability in low-Reynolds-number centrifugal compressors. The applicable method should increase performance by reducing drag, increasing blade loading, or reducing tip leakage. Based on the aerodynamic and structural demands, passive methods like riblets, squealers, winglets and grooves could be beneficial; however, the drawbacks of these approaches are that their performance depends on the operating conditions and the effect might be negative at higher Reynolds numbers. The flow control method, which would reduce the boundary layer thickness and reduce wake, could have a beneficial impact on the performance of a low-Reynolds-number compressor in the entire operating range, but none of the methods represented in this review fully fulfil this objective.